Pengalihan Fungsi Situs Warisan Dunia Hagia Sophia Menurut Konvensi Warisan Dunia 1972 - Devia Dewenia Matital; Dyah Ridhul Airin Daties (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Hagia Sophia is a historic building in Turkey and has been a UNESCO World Heritage Site since 1934 and has now been converted into a mosque by President Erdogan. UNESCO is the only United Nations agency that has a specific task of protecting cultural heritage which is under international control. The protection of the world's creativity and cultural diversity is contained in Article 7 of the 1972 World Heritage Convention.Purposes of the Research: This writing aims to examine and analyze how UNESCO functions in providing protection for World Heritage Sites whether the function of the Hagia Sophia World Heritage Site is contrary to the 1972 World Heritage Site Convention.Methods of the Research: The research method in this paper uses a normative juridical research type. The research approach used is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, journals and the writings of legal experts, as well as legal materials analysis techniques in this study using qualitative analysis techniques.Results of the Research: The results obtained are to explain that The results obtained show that, UNESCO as an organization that has a function to protect and preserve world culture is embodied in the 1972 World Heritage Site Convention, UNESCO is obliged to provide assistance in the form of funding, preservation in terms of technique and professional training, related to the transfer of the status of Hagia Sophia. does not conflict with the 1972 World Heritage Convention, because the convention does not yet regulate the Transfer of the Status of Historic Buildings. For this reason, it is suggested that in the 1972 World Heritage Convention there should be rules governing the Transfer of the Status of a Historic Building Site that is already included in a World Heritage Site, while respecting the principle of state sovereignty and in terms of the protection of a Building Site there must be cooperation between the government where the heritage is located. with UNESCO so that efforts to protect and preserve a Building Site can be carried out properly.